c-Jun Proto-Oncoprotein Plays a Protective Role in Lung Epithelial Cells Exposed to Staphylococcal α-Toxin - Moyano, Alejandro J.; Racca, Ana C.; Soria, Gastón; Saka, Héctor A.; Andreoli, Verónica; Smania, Andrea M.; Sola, Claudia; Bocco, José L. (Frontiers in Cellular and Infection Microbiology, 2018)
c-Jun is a member of the early mammalian transcriptional regulators belonging to the AP-1 family, which participates in a wide range of cellular processes such as proliferation, apoptosis, tumorigenesis and differentiation. Despite its established role in cell survival upon stress, its participation in the stress response induced by bacterial infections has been poorly investigated. To study the potential role of c-Jun in this context we choose the widely studied α-toxin produced by Staphylococcus aureus, a pore-forming toxin that is a critical virulence factor in the pathogenesis of these bacteria. We analyzed the effect of α-toxin treatment in the activation, expression and protein levels of c-Jun in A549 lung epithelial cells. Furthermore, we explored the role of c-Jun in the cellular fate after exposure to α-toxin. Our results show that staphylococcal α-toxin per se is able to activate c-Jun by inducing phosphorylation of its Serine 73 residue. Silencing of the JNK (c-Jun N-terminal Kinase) signaling pathway abrogated most of this activation. On the contrary, silencing of the ERK (Extracellular Signal-Regulated Kinase) pathway exacerbated this response. Intriguingly, while the exposure to α-toxin induced a marked increase in the levels of c-Jun transcripts, c-Jun protein levels noticeably decreased in the same time-frame as a consequence of active proteolytic degradation through the proteasome-dependent pathway. In addition, we established that c-Jun promoted cell survival when cells were challenged with α-toxin. Similarly, c-Jun phosphorylation was also induced in cells upon intoxication with the cytolysin produced by Vibrio cholerae in a JNK-dependent manner, suggesting that c-Jun-JNK axis would be a conserved responsive cellular pathway to pore-forming toxins. This study contributes to understanding the role of the multifaceted c-Jun proto-oncoprotein in cell response to bacterial pore-forming toxins, positioning it as a relevant component of the complex early machinery mounted to deal with staphylococcal infections.